2015
DOI: 10.1002/lary.25378
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care and short‐ and long‐term outcomes of laryngeal cancer care in the elderly

Abstract: 2c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Above all, higher quality is associated with lower complications, shorter length of stay, and less readmissions, ultimately leading to lower associated costs [25,[32][33][34][35][36][37]. Higher quality of care is better for patients but it is also cheaper for our health-care system, and during these trying economic times, we should strive to improve both.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Above all, higher quality is associated with lower complications, shorter length of stay, and less readmissions, ultimately leading to lower associated costs [25,[32][33][34][35][36][37]. Higher quality of care is better for patients but it is also cheaper for our health-care system, and during these trying economic times, we should strive to improve both.…”
Section: Resultsmentioning
confidence: 94%
“…In this cohort, prior to presentation at a tertiary care center, 43 % of patient's initial care deviated from guideline recommendations [24]. Using the SEER database and looking at a group of elderly patients with larynx cancer, Gourin et al demonstrated that patients receiving higher quality of care (i.e., higher compliance with guideline recommendations) were associated with improved survival on multivariate analysis [25]. This is the only study to link higher quality of care and adherence to guideline recommendations with outcomes.…”
Section: Beyond the Volume-outcome Relationshipmentioning
confidence: 96%
“…1215 What has been published for oral cavity cancer assesses compliance with a variety of metrics but does not correlate compliance with an outcome. 12 Published studies for larynx cancer have been limited to elderly patients, and most of the metrics were related to surveillance, management of recurrent disease, and end-of-life care.…”
Section: Discussionmentioning
confidence: 99%
“…12 Published studies for larynx cancer have been limited to elderly patients, and most of the metrics were related to surveillance, management of recurrent disease, and end-of-life care. 14,15 None of the above-referenced studies assessed how performance of specific quality metrics was associated with survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…914 The published studies 7,8 of quality metrics for laryngeal cancer have focused on elderly patients and included patients treated with surgical and nonsurgical approaches. In addition, the metrics were related primarily to surveillance, management of recurrent disease, and end-of-life care and did not find a graded response between increasing levels of compliance and the outcome of interest.…”
mentioning
confidence: 99%